2018
DOI: 10.1097/md.0000000000012144
|View full text |Cite
|
Sign up to set email alerts
|

Dexmedetomidine sedation combined with epidural anesthesia for laparoscopy in a patient with suspected tuberculosis

Abstract: We conclude that administration of dexmedetomidine combined with epidural anesthesia can provide comfortable sedation for short laparoscopic procedures in patients with suspected tuberculosis. This technique can minimize the risk of nosocomial infection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 9 publications
(8 reference statements)
0
1
0
Order By: Relevance
“…Dexmedetomidine is a new alpha (α) 2-adrenergic agonist with good anesthetic effects. Research has reported a stable patient condition without increased risks of adverse events such as respiratory depression after the administration of dexmedetomidine [5] . To this end, this study was undertaken to evaluate the effect of dexmedetomidine on patient recovery from anesthesia in gynecologic laparoscopic surgery.…”
mentioning
confidence: 99%
“…Dexmedetomidine is a new alpha (α) 2-adrenergic agonist with good anesthetic effects. Research has reported a stable patient condition without increased risks of adverse events such as respiratory depression after the administration of dexmedetomidine [5] . To this end, this study was undertaken to evaluate the effect of dexmedetomidine on patient recovery from anesthesia in gynecologic laparoscopic surgery.…”
mentioning
confidence: 99%